Analisis Tingkat Konsentrasi Belajar Matematika Siswa Kelas II Sd Negeri Selomanik Ditinjau Dari Usia Awal Masuk Sekolah - Kurniawati, Desti Shinta; Rahmawati, Puji (JURNAL PENDIDIKAN ROKANIA; Vol 8 No 1 (2023): Jurnal Pendidikan Rokania, 2023)
This study is entitled Analysis of Concentration Levels in Learning Mathematics for Second Grade Students at SD N Selomanik Kaliwiro Wonosobo in terms of Early School Entry Age. This study aims to determine whether the initial age of entering school affects the level of concentration in students' learning. This research is qualitative by observing the concentration level of students' learning when doing learning activities. The method used in this research is the method of interview and observation. The techniques used in this research are data collection, data reduction, data display, and verification and confirmation of conclusions. The result of this study is that the initial age of entering school is related to the level of concentration of students' learning, but this is not the main cause. The concentration of student learning is also related to the different abilities of children, different conditions of students, the learning environment, and of course the learning facilities that students get.